Immunization against full-length protein and peptides from the Lutzomyia longipalpis sand fly salivary component maxadilan protects against Leishmania major infection in a murine model. Issue 48 (4th December 2017) - Wheat, William H.; Arthun, Erik N.; Spencer, John S.; Regan, Daniel P.; Titus, Richard G.; Dow, Steven W.
Highlights: Vaccination against maxadilan (MAX) protect mice from aggravated Leishmania infection. Vaccination against MAX increases the number of IFN-γ-producing cells in draining lymph nodes. The peptide MAX-CLDC vaccine improves host immunity against MAX-mediated immune modulation. Abstract: Leishmaniasis is an arthropod vectored disease causing considerable human morbidity and mortality. Vaccination remains the most realistic and practical means to interrupt the growing number and diversity of sand fly vectors and reservoirs of Leishmania . Since transmission of Leishmania is achieved exclusively by sand fly vectors via immune-modulating salivary substances, conventional vaccination requiring an unmodified host immune response for success are potentially destined to fail unless immunomodulatory factors are somehow neutralized. Using cationic liposome DNA complexes (CLDC) as an adjuvant system along with Lu. longipalpis sand fly salivary component maxadilan (MAX) as antigen (Ag), we show that mice are protected from the MAX-induced exacerbation of infection with Leishmania major ( Lm ). The CLDC adjuvant and alum were comparable in terms of lesion induration and decreased parasite burden, however the alum adjuvant imposed more inflammation at the injection site. BALB/c, C3H and C57BL/6 mice vaccinated with MAX-CLDC containing either the full-length MAX or peptides spanning the N- and C-terminal regions of MAX are protected against footpad challenges with Lm co-injected with MAX. When compared to unvaccinated controls, all strains of mice immunized with CLDC containing either peptides encompassing the first 20 N-terminal AA or those spanning the last 15 AA of the C-terminal domain of MAX demonstrated decreased parasite burden after 9 or 18 weeks post challenge with Lm + MAX. MAX-CLDC immunized mice showed increased IFNγ-secreting and decreased IL-4-secreting CD4 + cells in footpad-draining lymph nodes. Antisera from C-terminal peptide (P11) MAX-CLDC-vaccinated animals was capable of recognizing FL-MAX and its C-terminal domain and also blocked MAX-mediated reprogramming of bone marrow-derived dendritic cells (BM-DC) in vitro. This peptide vaccine targeting sand fly MAX, improves host immunity against MAX-mediated immunomodulation.